Working Memory Updating Training Improves Mathematics Performance in Middle School Students With Learning Difficulties - Zhang, Hongxia; Chang, Lei; Chen, Xiaoying; Ma, Liang; Zhou, Renlai (Frontiers in Human Neuroscience, 2018)
Working memory (WM) deficit is considered the key cause of learning difficulties (LDs). Studies have shown that WM is plastic and thus can be improved through training. This positive effect is transferable to fluid intelligence and academic performance. This study investigated whether WM updating ability and academic performance in children with LDs could be improved through WM updating training and explored the effects of this training on the children’s brain activity. We used a running memory task lasting approximately 40 minutes per day for 28 days to train a group of 23 children with LDs (TLDs group). We also recruited two control groups of 22 children with LDs (CLDs group) and 20 children without LDs (normal control [NC] group). The behavioral results of a pretest indicated that WM updating ability and academic performance in the TLDs and CLDs groups were significantly lower than those in the NC group before training. Compared with the CLDs group, the TLDs group exhibited significant performance improvement in a 2-back WM task, as well as in mathematical ability. Event-related potential results suggested that the amplitudes of N160 (representative of visual recognition) and P300 (representative of updating processing, which is a valid index for updating WM) in the TLDs and CLDs groups were markedly lower than those in the NC group before training. In the TLDs group, these two components increased considerably after training, approaching levels similar to those in the NC group. The results of this study suggest that WM updating training can improve WM capability in children with LDs and the training effect can transfer to mathematical performance in such children. Furthermore, the participants’ brain activity levels exhibited positive changes. This paper provides experimental evidence that WM updating training could mitigate the symptoms of LDs to a certain degree.